The common diseases of freshwater ornamental fishes and the treatments applied by local fish owners in Puerto Princesa City, Palawan, Philippines - Mecha, Niño Jess Mar F.; Gonzales-Plasus, Maria Mojena (Journal of Fisheries, 2023)
The demand for freshwater ornamental fish as anti-stress pets and a source of livelihood had become popular in Puerto Princesa City (PPC), Palawan during the surge of COVID-19. However, the occurrence of many health-related issues become a major problem due to a lack of experience and knowledge of some fish owners engaged in freshwater ornamental fish keeping and breeding methods. This study was conducted on 13 local fish owners to determine the common diseases in freshwater ornamental fishes, affected species and their life stages and the treatments and preventive measures. A total of 19 diseases were recorded infecting the freshwater ornamental fishes in PPC. White-spot or ich disease was the most prominent disease, followed by tail and fin rot. Juvenile and adult of goldfish (Carassius auratus), Siamese fighting fish (Betta splendens) and guppy (Poecilla reticulata) were the most infected fishes, observed by 1 (7.7%) to 5 (38.5%) fish hobbyist. The salt bath was the most common treatment applied. Measures to increase the awareness of local fish hobbyist in terms of fish handling, breeding and health management is highly suggested to continuously improve and expand this developing fishery in Palawan as a source of income and pet companion.